Rencana Strategis Perpustakaan Sekolah : Pendekatan Praktis - Komarudin Komarudin (IAIN Ponorogo, 2012)
Environment always changes. it must be anticipated by thinking strategically, that is rethinking of the organization, its vision for the future. To acheive that vision requires mission. It also requires reexamining the organizaton's strenghts and weaknesses. Oraganization has to identify threats as well as opportunities that exist to encourage future diraction. This article explains strategic palnning practically especially that is implemented at school library.